Sixth Five Year Plan 1980-85 Andhra Pradesh Draft -Vol.III - Government of Andhra Pradesh (Government of Andhra Pradesh, 1980)
The Sixth Five-Year Plan (1980-85) for Andhra Pradesh presents a comprehensive strategy aimed at promoting socio-economic development across multiple sectors, with particular attention to agriculture, irrigation, infrastructure, education, health, and social welfare. With proposed outlays totaling approximately Rs. 410 billion and projected expenditures of Rs. 322 billion, the plan prioritizes increasing foodgrain production to 54.3 million tonnes, expanding irrigation coverage through major and medium projects like Vamsadhara, Nizamsagar, and Somasila, and improving water resource management to enhance agricultural yields and food security. Investments in rural roads, electrification, and flood control measures complement the infrastructure framework, while social programs target marginalized populations, including Scheduled Castes, Scheduled Tribes, and other disadvantaged groups, through housing, education, health services, scholarships, and vocational training. Employment generation, particularly via irrigation and rural development projects, is a key objective, supported by skill development for laborers and engineers. Centrally Sponsored Schemes further integrate agricultural development, marketing, and tourism initiatives to reinforce economic growth. Strategic emphasis is placed on inclusive development, modernization of irrigation systems, and sustainable maintenance practices, ensuring long-term resilience and operational efficiency. The plan embodies a holistic approach that aligns resource allocation with socio-economic priorities, aiming to foster equitable growth, enhance productivity, and strengthen the overall developmental trajectory of Andhra Pradesh.
Andhra Pradesh Finance and Planning Department
Andhra Pradesh Finance and Planning Department
Keywords: State Plan; Andhra Pradesh; Irrigation Projects; Agriculture Development; Rural Infrastructure; Social Welfare; Scheduled Castes; Scheduled Tribes; Employment Generation; Flood Control; Education and Health; Centrally Sponsored Schemes